Stem cell applications in intervertebral disc repair - Hiyama, A.; Mochida, J.; Sakai, D. (Cellular and Molecular Biology, 2008)
There is increasing rise of interest in stem cell therapy, as it provides new options for treating a broad range of diseases. Several experimental methods are being explored for the use of stem cells in delaying or reversing the degenerative process of the intervertebral disc, a major cause of low back pain. In this article, we review the current strategies for stem cell applications in intervertebral disc repair and present three novel approaches. These are, first, the activation of nucleus pulposus cells by co-culture with mesenchymal stem cells for autologous disc cell reinsertion; second, the in vitro induction of nucleus pulposus-like or annulus fibrosus-like cells from mesenchymal stem cells; and third, the in vivo induction study by direct transplantation of mesenchymal stem cells to the intervertebral disc induced to degenerate experimentally. Although still untested, stem cell therapy may become a major option in the treatment of intervertebral disc degeneration.